2012
DOI: 10.1080/13501763.2011.609710
|View full text |Cite
|
Sign up to set email alerts
|

Engaging with the EU in order to minimize its impact: sport and the negotiation of the Treaty of Lisbon

Abstract: The absence of explicit reference to sport in the EU Treaties has allowed the Court and the Commission room to require sport to adjust to the standards required by EU law. Sporting federations typically assert a need for a wider zone of autonomy than the Court and Commission have been prepared to grant, but, unable to persuade the Member States that they deserve exemption from the application of the Treaty, sports bodies have increasingly been induced to develop strategies of coexistence with the EU. This arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 12 publications
(2 reference statements)
0
19
0
Order By: Relevance
“…Even a casual internet search will further reveal that terms such as ''Lisbonisation'', ''Lisbonising'' and ''Lisbonised'' Kornbeck (2013a). 8 García and Weatherill (2012). 9 Brettschneider and Naul (2005) results of the first EU Work Plan, 16 all of which included specific HEPA-related proposals.…”
Section: Lisbonisation Without Regulation?mentioning
confidence: 97%
“…Even a casual internet search will further reveal that terms such as ''Lisbonisation'', ''Lisbonising'' and ''Lisbonised'' Kornbeck (2013a). 8 García and Weatherill (2012). 9 Brettschneider and Naul (2005) results of the first EU Work Plan, 16 all of which included specific HEPA-related proposals.…”
Section: Lisbonisation Without Regulation?mentioning
confidence: 97%
“…In the Lisbon Treaty however, the European Union has been equipped, for the first time, with a direct competence on sport, albeit only to 'to support, coordinate or supplement the actions of the Member States' (see Articles 6 and 165 of the treaty on the Functioning of the European Union) (C-306/06, Official Journal, 17-12-07, p.1),, which is the lowest level of competences attributed to the EU (see Weatherill 2010, García & Weatherill 2012. Whereas a 'direct' sport policy by the EU is still in its infancy (Tokarski et al 2004, García & Weatherill 2012, the impact of Article 165 on EU sports policy remains to be seen at this moment, but early legal and political analysis suggests that criteria for the application of EU competition law (which is of special interest in this article) are unlikely to be changed and, therefore, those aspects of EU sports policy will probably not suffer major modifications (Parrish et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Ironically, while many sports governing bodies continue deploying considerable efforts in defending their notion of a 'specificity' of sport (implying its idiosyncratic nature and incompatibility with rules complied with in other sectors), a 'political science of sport' will have to insist that it addresses the subject matter 'EU & sport' in basically the same way as other political phenomena, while at the same time arguing in favour of a sport-informed approach to this discourse -one which mainstream political science may be unlikely to deliver. Regarding the choice of disciplinary locus between the IR and Government branches of political science, recent research output has shown that a non-IR perspective can be very effective and convincing (e.g., García & Meier, 2012;García & Weatherill, 2012).…”
Section: The Implications Of 'Normality'mentioning
confidence: 99%